(untitled) (Journal of the College of Basic Education, 2022)
The research consisted of five chapters, including the first chapter, which highlights the impact of The use of some means of aesthetic education to assist in learning, such as rhythmic movement. It appears important Researching the identification of better teaching methods that help in the development of female students and qualify them in overcoming the difficulty of their performance. The second chapter included two main axes. The first included studies Theory As for the second axis, it included previous and similar studies, as the researcher presented a previous study